OPTIMIZATION OF JAVANESE LANGUAGE LEARNING THROUGH STORY ADVENTURE GAME - Maula Yudhananta, Naufal; WIJAYANTI, ESTI; CHAMID, AHMAD ABDUL (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This research addresses the critical decline in Javanese language usage among younger generations, with only 45% of Central Javanese children actively using the language in daily communication. The study aims to develop and evaluate